2019
DOI: 10.1093/mnras/stz2039
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relations for globular cluster systems in early-type galaxies

Abstract: The formation and growth of globular cluster systems (GCSs) is closely related to the evolutionary processes experienced by their host galaxies. In particular, their radial distributions scale with several properties of the galaxies and their halos. We performed a photometric study, by means of HST/ACS archival data of several intermediate luminosity galaxies located in low density environments. It was supplemented with available photometric data of GCSs from the Virgo and Fornax clusters, resulting in a sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 128 publications
2
20
0
12
Order By: Relevance
“…In the case of NGC 1172, its metallicity has not been studied in detail, but there is enough data to explore its colour. It has a magnitude of M g = −19.58 mag considering the distance adopted in this paper, and from Caso et al (2019b) we obtain (g − z ) 0 = 1.22 mag. Ferrarese et al (2006) analysed the colour-magnitude relation for a significant number of ETGs in the Virgo Cluster and, using this relation, we obtain an expected value of (g − z ) 0 = 1.45 mag for NGC 1172.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In the case of NGC 1172, its metallicity has not been studied in detail, but there is enough data to explore its colour. It has a magnitude of M g = −19.58 mag considering the distance adopted in this paper, and from Caso et al (2019b) we obtain (g − z ) 0 = 1.22 mag. Ferrarese et al (2006) analysed the colour-magnitude relation for a significant number of ETGs in the Virgo Cluster and, using this relation, we obtain an expected value of (g − z ) 0 = 1.45 mag for NGC 1172.…”
Section: Discussionmentioning
confidence: 51%
“…This fit does not take into account the flattening, which is why we also fit a modified version of the Hubble-Reynolds law (Binney & Tremaine 1987;Dirsch et al 2003), described in Equation 3. In Caso et al (2019b), the same modified Hubble profile is fitted only to the ACS sample (Cho et al 2012), and the parameters are consistent, as shown in 2.…”
Section: Radial Distributionmentioning
confidence: 77%
See 1 more Smart Citation
“…Adopting the approach suggested by van Dokkum et al (2016), we estimated the total population within 1.5R e . In addition, the total number of GCs within 5 R e , which is the upper limit for bound systems (Kartha et al 2014;Forbes 2017;Caso et al 2019), is also derived. Since the photometry reaches roughly the TOM peak, and assuming that the GCLF is also a Gaussian for the UDGs (e.g.…”
Section: Detection Of the Globular Clusters In Udgsmentioning
confidence: 99%
“…We find that the number of GC candidates over the ∼ 10.5 × 9.5 area around the UDG is ∼ 3.0 ± 3 arcmin −2 . The total number of GCs (N GC ) was derived within 1.5 R e , adopting the approach suggested by van Dokkum et al (2016), and also within 3 and 5R e , the higher value being close to the upper limit for bound systems (Forbes 2017;Caso et al 2019). All estimates were corrected for the contamination of foreground stars, background galaxies, and possible intra-cluster GCs, which is ∼ 3 sources/arcmin 2 , derived in the regions between 5 ≤ R ≤ 10 around the UDG.…”
Section: Appendix D: Search For Globular Clusters Around Udg 32mentioning
confidence: 99%